Modeling The Fiuctuational And Transformation Characteristics Of Peak Ground Level Ozone in Malaysian Ambient Air - Ramli , Nor Azam; Yahaya, Ahmad Shukri; Md Yusof, Nor Faizah Fitri; Mohamed, Nurul Izma (Universiti Sains Malaysia, 2016)
Ground level ozone (O3) is a noxious air pollutant that Imposed adverse effect to human health, crop yield and the environment. Hence, it is important to understand their fluctuation and transformation characteristic which is still regarded at its infancy stage in Malaysia to properly design abatement and control strategies. Therefore, this study aimed to Investigate the characteristics of O3 fluctuation and transformation from its precursors as well as to introduce the critical conversion point (COP) of O3 formation. Next hour O3 prediction models during daily, daytime, nighttime and critical conversion time were also developed using multiple linear regression and principal component regression to predict O3 concentrations in different group of monitoring stations. This study consists of 18 areas across Malaysia from 1999 to 2010. Although an ovenwhelming majority of the recorded data are below the prescribed levels in the Malaysian Ambient Air Quality Guidelines, total of 1,988 hour of exceedences have been recorded with majority contributed by Shah Alam. O3 diurnal cycles suggest a unimodal peak between 12 pm to 4 pm, while minimum concentration is consistently measured on 8 am. Results of PCA showed the contributions to O3 variation by NO2, NO, T and UVB is up to 80%, whereas the composite diurnal plots confirmed that variation is highly depend on NO2 and NO concentrations. The CCP of O3 formation were identified to occur in between 8 am to 11 am. MLR model based on cluster group during daily exhibited optimal performance in terms of coefficient of determination, prediction accuracy, and index of agreement with values of 0.9351, 0.9671 and 0.9831, respectively. Although the optimal model was during daily, the developed models using critical conversion time were more consistent with minimal differences between MLR and PGR in terms of error and accuracy. Effective ground level ozone control, need strategic, systematic and concerted efforts amongenvironmental related agencies in Malaysia